The chemical constituents of the ethyl acetate extract of the stems of Polyalthia Bullata / Mohd Afif Wasis - Wasis, Mohd Afif (Faculty of Applied Sciences, 2008)
Polyalthia Bullata is a plant that is traditionally effective as an aphrodisiac for men. In Malaysia, this plant is known as Tongkat Ali Hitam or Tongkat Ali Baginda. The stem bark of Polyalthia Bullata underwent successive solvent extraction using hexane, dichloromethane, ethyl acetate and methanol. The crude ethyl acetate extract was subjected to column and thin layer chromatography. Phytochemical analysis on the stem bark of Polyalthia Bullata yielded the known aporphine isoquinoline alkaloid, liriodenine. The compound was identified by UV, IR, GC-MS and NMR and compare with the literature. The weight and % yield of the compound were 3.8 mg and 0.4524 % respectively